IMPLEMENTATION OF THE VALUE OF RELIGIOUS MODERATION IN THE MIDST OF A MULTI-FAITH COMMUNITY: The Perspective of Multicultural Islamic Religious Education in Kapuas Hulu Regency - Rabuddin, Muhammad; Shomad, Abdus; Maskuri, Maskuri; Rohman, M. Djunaidi Ghony; Siregar, Irma Suryani (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
The implementation of religious moderation values in the midst of a multi-faith society in Kapuas Hulu Regency is important to strengthen harmony between religious communities. This regency is known for its high religious diversity so that in this context, multicultural Islamic religious education plays a strategic role in instilling the values of religious moderation. This study is included in the qualitative cluster by collecting observational data, interviews and documentation. In addition, researchers analyzed the data using data condensation, data display and drawing conclusions. The results of the study indicate that the implementation of religious moderation values in Islamic Religious Education in Kapuas Hulu Regency is very important to create a harmonious and peaceful society amidst diversity. Islamic Religious Education in Kapuas Hulu Regency has a strategic role in the implementation of religious moderation values, in the midst of a society that has high religious diversity. The values of religious moderation applied by the people of Kapuas Hulu Regency include a) tolerance, b) anti-violence, c) social justice and, d) inclusive attitudes so that they can make the people of Kapuas Hulu cooperate and respect each other. In addition, Kapuas Hulu Regency provides an understanding of the values of religious moderation through Islamic religious education such as a) religious tolerance education and b) understanding of religious moderation.